Surgical Presentation of Abdominal Tuberculosis at a University Hospital - Habib Ur Rehman Khan Toor, Shahida Baloch, Lal Shah, Mamona, Kashif Ali Shah, Shahnwaz Leghari (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine various surgical presentation of abdominal tuberculosis Study design: cross sectional study Place and duration: This study was conducted at Peoples University of Medical & Health Sciences for Women (PUMHS-W) Nawabshah Pakistan from October 2017 to march 2020. Methodology: The data in this study were from cases of abdominal TB that were admitted as an acute or subacute abdominal emergency. The data of the patients were analyzed using SPSS version 22. Descriptive analysis was used to examine the data. The data was presented using numbers and percentages. Results: Females made up 62.66 % of the 150 cases. A total of 55.33 % of the cases were between the ages of 30 and 50 years. No history of TB was shown in 60.66% of the cases and a history of pulmonary TB was found in 26.66 % of the cases. In 96.66% of patients, abdominal pain was present, followed by vomiting in 52 % and fever in 22 %. 60.66 percent of the cases were classified as having subacute intestinal obstruction, whereas 39.33 % had acute abdominal symptoms. The most common symptom was abdominal pain, and the most common clinical presentation was subacute intestinal obstruction. Early identification is crucial for avoiding intestinal TB's systemic and local effects. Conclusion: Intestinal obstruction was the most common clinical presentation of abdominal tuberculosis followed by intestinal obstruction. Acute abdominal TB is one of the most common causes of acute abdomen in endemic areas, as intestinal TB is a common extrapulmonary manifestation of TB. The key to avoiding systemic and local consequences of intestinal TB is early detection.